Biomass production, nutrients and root characteristics of fallow species and the utilization of its biomass as a phosphorus source for the common bean (Phaseolus vulgaris L.) - Jorge Mustonen, Pedro S. (2005)
Thesis (Ph.D.) - CATIE, Turrialba (Costa Rica) ; University of Wales, Bangor (RU), 2005